Embracing community-building in online classes to promote academic integrity - Çolak, Miranda Karjagdi; Glendinning, Irene (Leyla HARPUTLU, 2021)
Given that universities have transitioned to emergency remote teaching, academic integrity becomes a subject of ongoing inquiry. Students taking an English Preparatory Program (EPP) in universities aim to gain sufficient proficiency in English to continue with their courses in their departments. In an online teaching context, coping with requirements of the EFL (English as a foreign language) curriculum becomes a challenge for the students as students are deprived of their communities where they collaborate, interact and learn from each other. In this sense, teachers need to refocus not only on subject matter, but also ethical mores of academe and it is often simple day-to-day practices that build the community and establish a climate of integrity. While academic integrity has been researched extensively, more research is still needed about developing a learning community in online classes as a way to promote academic integrity. This investigation seeks to explore daily teaching practices towards community-building and analyse elements of the curriculum that work in favour of academic integrity in the context of emergency remote teaching. Six teachers and eighty EFL students (N=86) in an EPP of a state university in Turkey participated in the study. This case study drew upon an exploratory sequential mixed methods approach. The triangulation of the findings was carried out through a combination of various data sources. Qualitative data were collected through content analysis of course syllabi, assignment documents and policy statements, classroom self-observations; and focus groups with teachers and students. Quantitative data were gathered through a short survey with questions specifically designed for this context. Another aim of using the survey was to promote awareness on academic integrity among students. The results from multiple sources revealed that community-building not only facilitates positive collaboration in online classes, but also creates room for mutual trust and reduces chances of academic misconduct. Exploring results from the research can help faculty design measures to prevent academic dishonesty and eventually shape institutional policies. The positive implications for classroom practices of community-building towards academic integrity are discussed.